Haydn: the years of 'The Creation' 1796-1800 - Landon, H. C. Robbins 1926-2009 (London Thames and hudson, 1977)
The author treats the life and work of the composer in its chronological context, with detailed discussion, illustrated with musical examples, of the major works. The Chronicle is based principally on contemporary newspaper accounts, diaries and correspondence.In both its scale and complexity it is Haydn's greatest masterpiece - The Creation - which provides the major point of interest. The development of the work is traced from the libretto sketch by Baron Gottfried van Swieten which Haydn brought back from London, through the various stages of drafting (many of Haydn's preparatory sketches for the introduction - 'Chaos' - and various numbers in the Oratorio are reproduced as musical examples) to completion and first performance. Its subsequent publication, in 1800, and circulation to subscribers all over Europe was supervised by Haydn himself, and his list of the original subscribers is included as an appendix to the main discussion of the work which was to prove the crowning achievement of the composer's career up to the turn of the century.